In the Shadow of the ‘Big House' Redefining halfway houses within the debate over incarceration - May, Andrew (Department of Public Law, 2024)
Incarceration is a paradox. It creates an artificial convergence of intense and opposing social forces. Prison dominates every aspect of an inmate's life under the auspices of preparing them for a chaotic transition to a society governed by flexibility and choice. Somehow control and conformity are expected to prepare inmates to re-join communities with neither of these characteristics. While prison has the stated goal of rehabilitation, it has always been a barrier for inmates seeking to build new lives for themselves. Meaningful restoration demands a different institutional setting. In the 19th century, pre-release residential programmes, also known as ‘halfway houses', were created to deal with the challenges of prisoner integration. These rehabilitation programmes for ex-prisoners attempted to bridge the gap between rigid institutions and a world that confronts ex-prisoners with an overwhelming array of decisions and responsibilities. This thesis surveys the trauma of incarceration before exploring the potential for halfway houses. In an environment where rehabilitation or training programmes are increasingly specialised, halfway houses are attempting a holistic programme. While they may fail in their mandate, these residential programmes at least recognise the difficulties in overcoming carceral trauma. This thesis will use South Africa's halfway houses and some comparative international data to study prisoners' struggle to integrate into a hostile society and the institutions that guide them. What does it mean to be ‘halfway' inside a total institution? Ex-prisoners are caught between two worlds, and halfway houses inhabit this place of conflict. This thesis will situate halfway houses within the larger theoretical debate between punishment and rehabilitation, and then propose several reform initiatives that will better utilise their potential. The first four chapters represent the weight of incarceration on our sociopolitical landscape and the prisoners' lives. Erving Goffman's concept of “total institutions” is foundational to these chapters, because it is impossible to understand rehabilitation without contending with the institutional deadweight of incarceration. The last four chapters present my ethnographic research into four South African case studies, and explore the theoretical and practical implications for halfway houses within the Department of Correctional Services. Incarceration will always resist reform, but it is possible to pry inmates away from its grip if there is an alternate institutional context. This thesis is about narrowing the frame of reference to a small institutional setting. Innovation and reform are not possible until the lived experience of prisoners has been revealed. Halfway houses are small-scale initiatives on the periphery of the criminal justice system, which is exactly why they are an ideal context for reform.